2019
DOI: 10.1080/09593985.2018.1564095
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various respiratory physiotherapies after lung resection: a systematic review

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In contrast to Gu et al 23 , no systematic increment of θ R and decrement of θ L was observed in the LUL post-operative cases, possibly because of the limited size of our population. Although the characterization and the role of structural modifications on post-operative pulmonary function is still an open field of research 36 , the pre and post-operative values measured angles in our study are in line with the expected intersubject variability, also accounting for the sex-related differences between women and men 37 .…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to Gu et al 23 , no systematic increment of θ R and decrement of θ L was observed in the LUL post-operative cases, possibly because of the limited size of our population. Although the characterization and the role of structural modifications on post-operative pulmonary function is still an open field of research 36 , the pre and post-operative values measured angles in our study are in line with the expected intersubject variability, also accounting for the sex-related differences between women and men 37 .…”
Section: Discussionsupporting
confidence: 86%
“…The effect of standard respiratory physiotherapy on long-term postoperative complications after lung resection is still an investigation subject, and the role of each structural modification on postoperative pulmonary function is not entirely clear. 51 As already mentioned, regional ventilation globally redistributes to the contralateral side after lobectomy, and the remaining lobes receive a greater flow rate as a compensatory response. Clinical studies reported a decrease in spirometry parameters (FVC and FEV1) after lobectomy, indicating an overall reduction of pulmonary function.…”
Section: Lobementioning
confidence: 89%
“…The effect of standard respiratory physiotherapy on long‐term postoperative complications after lung resection is still an investigation subject, and the role of each structural modification on postoperative pulmonary function is not entirely clear. 51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boutron and Ravaud 2018). Quantitative interrogation is limited to isolated questions such as whether in a particular case it is better to opt for one exercise or another (eg, flexion vs extension) or how many therapeutic interventions should be recommended (cf., eg, Larsen et al . 2020; Ojha et al .…”
Section: Background: Overview Of Contemporary Theorisations Of Physio...mentioning
confidence: 99%